KOMPETENSI PEDAGOGIK GURU DALAM MENUMBUHKAN MOTIVASI BELAJAR PESERTA DIDIK - Siti Suwaibatul Aslamiyah; Abdul Manan (Universitas Islam Lamongan, 2019)
Teachers play a major role in developing education, especially those that are organized formally in schools. Teacher's work products become a symbol of the progress of civilization. This means that teacher professionalism is the basis of educational progress. They are professional educators with the main task of educating, teaching, guiding, directing, training, and evaluating students in any formal education. In carrying out these main tasks, teachers are required to have expertises in their field. The main task will be effective if the teacher has competencies (pedagogic competence, personality competence, professional competence, and social competence). These competencies must be implemented in the learning process (instructional) in which the student component is a very important factor. In the learning process students are expected to be able to receive messages or learning materials from their teachers. To be able to receive learning materials from teachers, one of which is the need for motivation that could be fostered by professional teachers who have pedagogic competence.